2022
DOI: 10.1002/alr.22954
|View full text |Cite
|
Sign up to set email alerts
|

Health‐care utilization for sinusitis after pneumococcal vaccination in patients with low antibody titers

Abstract: Background: Pneumococcal antibody deficiency has been the subject of limited study in chronic rhinosinusitis (CRS) and has not been studied in recurrent acute rhinosinusitis (RARS). The 23-valent pneumococcal polysaccharide vaccine (PPSV23) is considered for patients with nonprotective Streptococcus pneumoniae titers. We hypothesized that both RARS and CRS patients with deficient S pneumoniae titers and subsequent PPSV23 vaccination would have reduced health-care encounters for sinusitis and fewer prescription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…This yielded a total of 42 papers included in the systematic review (Figure 1). 8–49 The Oxford levels of evidence assigned included eight level 3 studies, and 34 level 4 studies, encompassing case series/retrospective reviews, case–control, and prospective studies. Additionally, four systematic reviews related to this topic were identified 4,5,50,51 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This yielded a total of 42 papers included in the systematic review (Figure 1). 8–49 The Oxford levels of evidence assigned included eight level 3 studies, and 34 level 4 studies, encompassing case series/retrospective reviews, case–control, and prospective studies. Additionally, four systematic reviews related to this topic were identified 4,5,50,51 .…”
Section: Resultsmentioning
confidence: 99%
“…However, no details were reported on the type, frequency, and duration of the antibiotics given. Prophylactic antibiotics was reported to be used in addition to IVIG in two studies without mentioning details about its impact on the frequency of sinus infections 11,44 . Bondioni et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations